Belgium : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2000)
Measuring the size of the underground economy is obviously a difficult task. This paper reviews the literature, as applied to Belgium and elsewhere, on the determinants of the gray economy. The methods that have been used to measure the size of the gray economy are also discussed. The estimates for Belgium are updated using the currency demand approach. The major theory of the gray economy focuses on taxes, which drive a wedge between net incomes and gross labor costs.